Immediate effect of virtual reality intervention on task related neck pain and muscle fatigue in dentists - Menon, Shabarish; Dabholkar, Twinkle; Shripad, Isha (International Journal Of Community Medicine And Public Health, 2023)
Background: Dentistry requires long hours of static body postures while executing activities in which permanently forced loads influence the musculoskeletal system. Methods: 25 dentists were recruited where neck pain or fatigue was assessed subjectively using NRS and Borg CR10 scale respectively and the pain pressure threshold of the upper trapezius muscle was assessed objectively using a handheld algometer pre- and post- intervention. Mobile VR game- Froggy VR was administered as a virtual reality. Results: A Wilcoxon signed rank test showed a statistically significant reduction in the intensity of task related neck pain and fatigue post VR intervention with Z-score=-4.549, n=38, p<0.001 and Z-score=-4.588, n=38, p<0.001 respectively. Also, there was a statistically significant increase in the pain pressure threshold of the right and left upper trapezius muscle post VR intervention with Z-score=-4.937, n=38, p<0.001 and Z-score=-4.512, n=38, p<0.001 respectively. Conclusions: Virtual reality intervention led to an immediate reduction in task-related neck pain and muscle fatigue among dentists with an immediate reduction in pain sensitivity of the upper trapezius muscle in dentists.